32.1k views
0 votes
How would i simplify this?

How would i simplify this?-example-1
User Kerni
by
6.1k points

2 Answers

4 votes

Answer:

3^6-4x=3^3x-3

Explanation:

9^3-2x = 27^x-1 ( 9 is 3² and 27 is 3³)

(3²)^3-2x= (3³)^x-1 in case of exponential between brackets , multiply the exponents.

3^6-4x=3^3x-3

User AlexStack
by
5.6k points
3 votes

Answer:

x = 9/7

Step-by-step explanation:

9^3-2x = 27^x-1

(3^2)^3-2x = (3^3)^x-1

3^2(3-2x) = 3^3(x-1)

2(3-2x) = 3(x-1)

2(-2x+3) = 3x - 3

-4x + 6 = 3x - 3

-4x = 3x - 9

-7x = -9

x = -9/-7

x = 9/7

User Salmin Skenderovic
by
5.9k points